The Effect of The Number of Section on The Growth of Vanilly Plant Cuttings (Vanilla planivolia Andrews) - Badaria, Badaria; Amane, Gusmin Syarif; Elsabet, Elsabet; Yanti, Yanti; Aba, La (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The vanilla plant (Vanilla planifolia Andrews) is one of a spice plants that has economic value and the global demand for vanilla continues to increase along with the development of industries that rely on vanilla raw materials. One of the factors that contributing to the vanilla low production is the limited availability of cuttings as a source of section. One effort required to increase vanilla plant production is by using good section as well as paying attention to the number of segments on vanilla plant cuttings. This research aims to determine the effect of the number of segments on the growth of vanilla plant cuttings (Vanilla planifolia Andrews). The experimental design used in this research was a Completely Randomized Design (CRD) which consisted of 5 treatments and 3 replications so that there were 15 treatment units, namely R1 = 1 segment, R2 = 2 segments, R3 = 3 segments, R4 = 4 segments, and R5 = 5 segments. The observational data from the treatment was processed statistically. If the results of the analysis have a real effect then a further test is carried out with BNJ at a real level of 5%. The parameters observed were shoot height (cm), number of leaves (strands), and shoot diameter (cm). The results of the research showed that the treatment of the number of cutting segments had a very significant effect on the growth parameters of shoot height, number of leaves and shoot diameter of vanilla plant seedlings with the best treatment obtained in the R4 treatment (4 segments).